CARBON ISOTOPE STRATIGRAPHY OF THE DEVONIAN OF CENTRAL AND SOUTHERN EUROPE - Buggisch W.; Joachimski M.M. (My University, 2006)
Carbonate rocks of the Rhenohercynian and Saxothuringian zones of the Variscan Mountains, Prague Syncline, Carnic Alps, Montagne Noire, Pyrenees, and Cantabrian Mountains were investigated for δ13Ccarb. The values were measured on bulk carbonate, selected carbonate components and cements. Many of the studied carbonates are interpreted to exhibit primary marine δ13C values with only some showing evidence of diagenetic alteration. A δ13C curve is presented for the entire Devonian time interval. Positive δ13C excursions are documented in the woschmidti-postwoschmidti, sulcatus, kitabicus, Upper serotinus, kockelianus, Middle varcus, falsiovalis, Upper rhenana, linguiformis to Middle triangularis, and Middle to Upper praesulcata conodont Zones. Some excursions are recorded worldwide and interpreted to be of global significance as e.g. at the Silurian-Devonian and Frasnian-Famennian boundaries. Some of the others are described for the first time from Central and Southern Europe, and their global nature has to be verified by further investigations. Most δ13C excursions coincide with sea-level changes and the deposition of black shales. A coupling of changes in sea-level, weathering intensity, nutrient supply, organic carbon production, and climate is assumed as driving force of the carbon isotope excursions. © 2006 Elsevier B.V. All rights reserved.
Keywords: BIOEVENTS; BLACK SHALE; CANTABRIAN MOUNTAINS; CARBON ISOTOPES; CARNIC ALPS; DEVONIAN; MONTAGNE NOIRE; PRAGUE SYNCLINE; RHENOHERCYNIAN; SAXOTHURINGIAN; Paleozoic::Devonian; Палеозой::Девонская